Positive electrode active material, positive electrode plate, and non-aqueous electrolyte secondary battery

By using a positive electrode active material composed of a small-particle-size lithium transition metal composite oxide first active material and a large-particle-size lithium transition metal composite oxide second active material, and by adding carbon nanotubes to the positive electrode active material layer, the problem of insufficient volumetric energy density and input-output characteristics in non-aqueous electrolyte secondary batteries is solved, thereby improving battery performance.

CN120933308APending Publication Date: 2025-11-11PRIME PLANET ENERGY & SOLUTIONS INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510585446.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-05-09
Filing Date
2025-05-08
Publication Date
2025-11-11

AI Technical Summary

Technical Problem

In existing non-aqueous electrolyte secondary batteries, it is difficult to simultaneously improve the volumetric energy density and input-output characteristics of the positive electrode active material.

Method used

The positive electrode active material is composed of a first active material of small-particle-size lithium transition metal composite oxide and a second active material of large-particle-size lithium transition metal composite oxide. Multiple primary particles are aggregated to form secondary particles, and carbon nanotubes are added to the positive electrode active material layer to improve electronic conductivity.

Benefits of technology

This technology improves the volumetric energy density and input/output characteristics of non-aqueous electrolyte secondary batteries, reduces the diffusion distance of lithium ions, enhances electronic conductivity, and improves the battery's charging capacity and cycle characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005391567090000131
    Figure BDA0005391567090000131
Patent Text Reader

Abstract

The invention relates to a positive electrode active material, a positive electrode plate, and a non-aqueous electrolyte secondary battery. The positive electrode active material includes a first active material represented by formula (I) and a second active material represented by formula (II). Each of the first active material and the second active material is a secondary particle formed by aggregating 50 or more primary particles. The average particle diameter (D150) of the first active material is smaller than the average particle diameter (D250) of the second active material. Li < 1 + a < 1 > Ni < x > < 1 > Mn < y > < 1 > M < 1 > z < 1 > O2 (I); and Li < 1 + a < 2 > Ni < x > Mn < y > M < 2 > z < 2 > O < 2 > (II).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode active material, a positive electrode plate comprising the positive electrode, and a non-aqueous electrolyte secondary battery having a positive electrode plate. Background Technology

[0002] In secondary batteries, it is known to use a positive electrode plate in which a lithium transition metal composite oxide, which serves as the positive electrode active material, is incorporated into the current collector. Japanese Patent Application Publication No. 2012-59527 discloses a positive electrode for secondary batteries comprising two lithium transition metal composite oxides with different molar ratios of lithium to a transition metal. Summary of the Invention

[0003] The purpose of this disclosure is to provide a positive electrode active material that can improve volumetric energy density and achieve good input-output characteristics in a non-aqueous electrolyte secondary battery, a positive electrode plate comprising the positive electrode plate, and a non-aqueous electrolyte secondary battery having the positive electrode plate.

[0004] [1] A positive electrode active material comprising a first active material represented by the following formula (I) and a second active material represented by the following formula (II), wherein the first active material and the second active material are both secondary particles formed by the aggregation of more than 50 primary particles, and the average particle size (D150) of the first active material is smaller than the average particle size (D250) of the second active material.

[0005] Li 1+a1 Ni x1 Mn y1 M1 z1 O2 (I)

[0006] Li 1+a2 Ni x2 Mn y2 M2 z2 O2 (II)

[0007] In equations (I) and (II),

[0008] M1 and M2 are each independently one or more metallic elements selected from Co, Al, Mg, Ca, Ti, V, Cr, Fe, Cu, Zn, Zr, Nb, Mo, Ta, and W.

[0009] Given the conditions 0.13≤a1≤0.33, 0≤x1≤0.3, 0.47≤y1≤0.67, and 0≤z1≤0.3, the expression a1+x1+y1+z1=1 is satisfied.

[0010] Given the conditions -0.1≤a²≤0.1, 0.6≤x²≤1, 0≤y²≤0.3, and 0≤z²≤0.3, we have a²+x²+y²+z²=1.

[0011] [2] According to the positive electrode active material described in [1], wherein the average particle size (D150) of the first active material is 1 to 4 μm.

[0012] [3] According to the positive electrode active material described in [1] or [2], wherein the average particle size (D250) of the second active material is 2 to 15 μm.

[0013] [4] The positive electrode active material according to any one of [1] to [3], wherein the ratio (D250 / D150) of the average particle size of the second active material to the average particle size of the first active material is 2 or more.

[0014] [5] The positive electrode active material according to any one of [1] to [4], wherein the content of the first active material is 60 to 95% by mass.

[0015] [6] A positive electrode plate having a positive electrode active material layer comprising a positive electrode active material according to any one of [1] to [5].

[0016] [7] According to the positive electrode plate of [6], the positive electrode active material layer further comprises carbon nanotubes, and the content of the carbon nanotubes is 2 to 6 by mass relative to the total amount of the first active material in the positive electrode active material layer.

[0017] [8] A non-aqueous electrolyte secondary battery comprising an electrode body having a positive electrode plate according to [6] or [7].

[0018] [9] According to the non-aqueous electrolyte secondary battery described in [8], the electrode body further comprises a negative electrode plate having a negative electrode active material layer, the negative electrode active material layer comprising a negative electrode active material, the negative electrode active material comprising a carbon-based active material and an active material containing Si.

[0019]

[10] According to the non-aqueous electrolyte secondary battery of [9], the content of the Si-containing active material in the negative electrode active material is 3 to 15% by mass relative to the total amount of the negative electrode active material.

[0020]

[11] According to the non-aqueous electrolyte secondary battery of [9] or

[10] , wherein the active material containing Si is selected from one or more of Si, SiOx and SiC, wherein x = 0.5 to 1.5.

[0021] The above and other objects, features, aspects and advantages of the present invention will become apparent from the following detailed description relating to the present invention. Detailed Implementation

[0022] In this specification, unless otherwise specified, the numerical ranges such as "x~y" include both upper and lower limits. That is, "x~y" represents a numerical range "above x and below y". A value arbitrarily selected from the numerical range can be set as a new upper or lower limit. For example, a new numerical range can be set by arbitrarily combining values ​​within the numerical range with values ​​recorded in other parts of this specification or tables.

[0023] (Positive electrode active material)

[0024] The positive electrode active material of this embodiment (hereinafter also referred to as "this positive electrode active material") is used in the positive electrode plate of non-aqueous electrolyte secondary batteries (hereinafter also referred to as "secondary batteries") such as lithium-ion batteries.

[0025] This positive electrode active material includes a first active material represented by the following formula (I) and a second active material represented by the following formula (II).

[0026] Li 1+a1 Ni x1 Mn y1 M1 z1 O2 (I)

[0027] Li 1+a2 Ni x2 Mn y2 M2 z2 O2 (II)

[0028] In equations (I) and (II),

[0029] M1 and M2 are each independently one or more metallic elements selected from Co, Al, Mg, Ca, Ti, V, Cr, Fe, Cu, Zn, Zr, Nb, Mo, Ta, and W.

[0030] Given the conditions 0.13≤a1≤0.33, 0≤x1≤0.3, 0.47≤y1≤0.67, and 0≤z1≤0.3, the condition a1+x1+y1+z1=1 is satisfied.

[0031] Given the conditions -0.1≤a²≤0.1, 0.6≤x²≤1, 0≤y²≤0.3, and 0≤z²≤0.3, we have a²+x²+y²+z²=1.

[0032] Both the first and second active substances are secondary particles formed by the aggregation of more than 50 primary particles. The average particle size (D150) of the first active substance is smaller than that of the second active substance (D250).

[0033] Based on this positive electrode active material, in secondary batteries, the volumetric energy density can be improved, and good input-output characteristics can be achieved.

[0034] The first active material is a lithium transition metal composite oxide. The first active material is a lithium-excess type positive electrode active material with a high Li content. The first active material can be any compound represented by formula (I) above. In formula (I), M1 preferably contains one or more of Co, Al, Mg, Ti, and Fe, more preferably Co. In formula (I), a1 can be 0.14 ≤ a1 ≤ 0.30, 0.15 ≤ a1 ≤ 0.25, or 0.16 ≤ a1 ≤ 0.20. In formula (I), x1 can be 0.00 ≤ x1 ≤ 0.30, 0.00 < x1 ≤ 0.25, 0.05 ≤ x1 ≤ 0.20, or 0.10 ≤ x1 ≤ 0.17. In equation (I), y1 can be 0.48≤y1≤0.65, 0.50≤y1≤0.67, or 0.50≤y1≤0.60. In equation (I), z1 can be 0.00≤z1≤0.30, 0.00<z1≤0.25, 0.05≤z1≤0.20, or 0.10≤z1≤0.18.

[0035] The second active material is a lithium transition metal composite oxide. The second active material is a positive electrode active material with a high Ni content. The second active material can be any compound represented by formula (II) above. In formula (II), M2 preferably contains one or more of Co, Al, Mg, Ti, and Fe, and more preferably contains Co. In formula (II), a2 can be -0.10 ≤ a2 ≤ 0.10, -0.08 ≤ a2 ≤ 0.08, -0.05 ≤ a2 ≤ 0.05, or -0.02 ≤ a2 ≤ 0.02. In formula (II), x2 can be 0.60 ≤ x2 ≤ 1.00, 0.65 ≤ x2 < 11.00, 0.70 ≤ x2 ≤ 0.95, 0.75 ≤ x2 ≤ 0.90, or 0.78 ≤ x2 ≤ 0.85. In equation (II), y2 can be 0.00≤y2≤0.30, 0.00<y2≤0.30, 0.05≤y2≤0.20, or 0.07≤y2≤0.15. In equation (II), z2 can be 0.00≤z2≤0.30, 0.00<z2≤0.30, 0.05≤z2≤0.20, or 0.07≤z2≤0.17.

[0036] The composition of the first and second active substances can be determined, for example, by ICP (inductively coupled plasma) luminescence spectrophotometry.

[0037] The first and second active substances are secondary particles formed by the aggregation of more than 50 primary particles. The number of primary particles aggregated in the secondary particles of both the first and second active substances can independently be more than 100 or more than 1000, but is typically 5 × 10⁻⁶. 6If less than one, it can be 5×10 5 The number of primary particles aggregated in the first active substance and the number of primary particles aggregated in the second active substance may be the same or different. For example, the number of primary particles aggregated in the first active substance may be greater or less than the number of primary particles aggregated in the second active substance. In this specification, the number of primary particles aggregated can be confirmed using, for example, SEM images obtained using a scanning electron microscope (hereinafter also referred to as "SEM").

[0038] The first active material is composed of secondary particles formed by the aggregation of multiple primary particles, resulting in a large specific surface area and improved specific capacity, thus facilitating an increase in the volumetric energy density of the secondary battery. The second active material, also composed of secondary particles formed by the aggregation of multiple primary particles, allows for a shorter diffusion distance of lithium ions within the particles constituting the second active material compared to a single-particle design. Furthermore, the lithium ion diffusion path is simplified. Therefore, by including the second active material in the positive electrode active material, a secondary battery with excellent input-output characteristics can be easily obtained.

[0039] The average particle size (D150) of the first active substance is smaller than the average particle size (D250) of the second active substance. In this specification, the average particle size (D150) and average particle size (D250) are the cumulative frequencies of the smaller particle size side in the volume-based particle size distribution, representing the 50% of the particle sizes. The volume-based particle size distribution can be measured using a laser diffraction particle size distribution measuring device.

[0040] Compared to the second active material, the first active material has a larger specific capacity and lower lithium ion diffusivity within it. Therefore, by making the average particle size (D150) smaller than the average particle size (D250), the diffusion distance of lithium ions within the particles constituting the first active material can be reduced. This makes it easier to obtain a secondary battery with good input-output characteristics.

[0041] The ratio (D250 / D150) of the average particle size of the second active substance to the average particle size of the first active substance can be 2.0 or more, preferably 2 or more, preferably 2.2 or more, and typically 7.0 or less. The ratio (D250 / D150) can be 2.0 to 7.0, 2.2 to 6.5, 2.4 to 6.0, 2.5 to 5.8, or 3.0 to 5.0.

[0042] If the ratio (D250 / D150) decreases, the difference between the average particle size of the first active material and the average particle size of the second active material decreases. Therefore, the filling capacity of the first and second active materials decreases, and the porosity when forming the positive electrode active material layer using these materials increases. Consequently, the electron conductivity in the positive electrode active material layer decreases, and the input / output characteristics of the secondary battery tend to deteriorate. If the ratio (D150 / D250) is within the aforementioned range, it is easier to obtain a secondary battery with good input / output characteristics.

[0043] The average particle size (D150) of the first active substance can be 1.0–4.0 μm, preferably 1–4 μm, and can be 1.5–3.5 μm or 2.0–3.0 μm. The average particle size (D250) of the second active substance can be 2.0–15.0 μm, preferably 2–15 μm, more preferably 6.0–15.0 μm, and can be 7.0–14.0 μm or 8.0–12.0 μm.

[0044] In this positive electrode active material, the content of the first active material is preferably greater than the content of the second active material. The content of the first active material in this positive electrode active material is preferably 60-95% by mass, more preferably 65-90% by mass, and may be 70-85% by mass or 75-82% by mass.

[0045] Compared to the second active material, the first active material has a larger specific capacity but a higher resistivity. If the content of the first active material increases, the resistivity of the positive electrode active material increases due to the higher proportion of the first active material, and electronic conductivity tends to decrease. Furthermore, if the proportion of the first active material increases, the filling capacity of both the first and second active materials tends to decrease. Consequently, the compressibility during the formation of the positive electrode active material layer decreases, and the porosity of the positive electrode active material layer tends to increase. If, as described above, electronic conductivity decreases and the porosity of the positive electrode active material layer increases, the input-output characteristics of the secondary battery tend to decrease. If the content of the first active material decreases, the proportion of the second active material increases, and the volumetric energy density of the secondary battery tends to decrease. If the content of the first active material is within the above-mentioned range, a secondary battery with good input-output characteristics and improved volumetric energy density can be easily obtained.

[0046] In the positive electrode active material, the content of the second active material can be 5-40% by mass, 10-35% by mass, 15-30% by mass, or 18-25% by mass. The content of the first active material and the content of the second active material refer to the amount when the total amount of the positive electrode active material is set to 100% by mass.

[0047] This positive electrode active material may contain only the first active material and the second active material, or it may further contain other active materials besides the first and second active materials. The total content of the first and second active materials in this positive electrode active material, relative to the total amount of this positive electrode active material, may be 85-100% by mass, 90-100% by mass, 92-99% by mass, or 95-98% by mass.

[0048] (Positive electrode plate)

[0049] The positive electrode plate of this embodiment (hereinafter also referred to as "this positive electrode plate") is used in a secondary battery. This positive electrode plate has a positive electrode active material layer containing this positive electrode active material. Because this positive electrode plate contains this positive electrode active material, it is possible to improve the volumetric energy density and achieve good input-output characteristics in a secondary battery.

[0050] This positive electrode plate can have a positive electrode active material layer on one or both sides of the positive electrode current collector foil. The positive electrode current collector foil is, for example, a metal foil made of aluminum materials such as aluminum and aluminum alloys. In addition to the positive electrode active material itself, the positive electrode active material layer further includes at least one of a conductive additive and a binder material, preferably both a conductive additive and a binder material.

[0051] Examples of conductive additives include carbon materials. Carbon materials may include one or more selected from fibrous carbon, carbon black (acetylene black, Ketjen black, etc.), coke, and activated carbon. Fibrous carbon may include carbon nanotubes (hereinafter also referred to as "CNTs"). CNTs may be single-layer carbon nanotubes (SWCNTs), double-layer carbon nanotubes (DWCNTs), or other multilayer carbon nanotubes. The conductive additive may include one or more of the above-mentioned conductive additives.

[0052] The positive electrode active material layer preferably contains CNTs in addition to the positive electrode active material itself. The CNT content relative to the total amount of the first active material in the positive electrode active material layer can be 2.0 to 6.0% by mass, preferably 2 to 6% by mass, can be 2.2 to 5.8% by mass, can be 2.5 to 5.6% by mass, more preferably 2.7 to 5.5% by mass, can be 3.0 to 5.0% by mass, and can be 3.5 to 4.5% by mass.

[0053] In the first active material, oxygen atoms sometimes detach and generate oxygen as lithium ions are adsorbed and released. Oxygen generated from the first active material easily causes oxidative decomposition of the non-aqueous electrolyte in the secondary battery. Because the first active material has a high Li content, if oxidative decomposition of the non-aqueous electrolyte occurs, the exchange between lithium ions and hydrogen ions is promoted, easily leading to structural changes in the first active material. These structural changes can cause a decrease in the capacity and cycle performance of the secondary battery. If the CNT content is within the aforementioned range, the amount of hydrogen ion adsorbed by CNTs increases, and the exchange reaction between lithium ions and hydrogen ions is suppressed, thus easily suppressing the decrease in the cycle performance of the secondary battery. Furthermore, CNTs enhance the electronic conductivity of the positive electrode active material; therefore, if the CNT content is within the aforementioned range, it can suppress the decrease in the charging capacity of the secondary battery and increase the volumetric energy density. If the CNT content increases, the porosity of the positive electrode active material layer decreases, reducing the diffusion of lithium ions, thus easily reducing the charging capacity of the secondary battery and making it difficult to improve the volumetric energy density. If the CNT content decreases, it becomes difficult to enhance the electronic conductivity of the primary active material with high resistance, thus the input-output characteristics of the secondary battery are easily reduced.

[0054] The CNT content in the positive electrode active material layer relative to the total amount of the positive electrode active material can be 1.7–6.0% by mass, 2.0–5.0% by mass, or 2.5–4.0% by mass.

[0055] Examples of adhesive materials include fluoropolymers such as polyvinylidene fluoride (PVdF) and polytetrafluoroethylene (PTFE); polyacrylonitrile (PAN); polyimide; acrylic resins; polyolefins; cellulose resins such as carboxymethyl cellulose (CMC), methyl cellulose (MC), and hydroxypropyl cellulose; and polyethylene oxide (POE). An adhesive material may contain one or more of the above-mentioned adhesive materials.

[0056] This positive electrode plate can be obtained, for example, by forming a positive electrode active material layer on a positive electrode current collector foil. For instance, this positive electrode plate is obtained by coating a positive electrode slurry containing this positive electrode active material onto the positive electrode current collector foil, drying it, and then compressing it to form a positive electrode active material layer. In addition to the positive electrode active material, the positive electrode slurry may contain a binder, a conductive additive, and a solvent such as N-methyl-2-pyrrolidone (NMP).

[0057] (Non-aqueous electrolyte secondary battery)

[0058] The non-aqueous electrolyte secondary battery (hereinafter also referred to as "this battery") of this embodiment has this positive electrode plate. Because this battery has this positive electrode plate, it can improve the volumetric energy density and has good input-output characteristics.

[0059] This battery can include an electrode body containing a positive electrode plate and a non-aqueous electrolyte, and can include a battery casing that houses the electrode body and the non-aqueous electrolyte. The battery casing may include: an outer packaging body with an opening, and a sealing plate that seals the opening. The outer packaging body and the sealing plate are preferably made of metal, and can be formed using aluminum, aluminum alloy, iron, or iron alloy, etc. A resin sheet serving as an electrode support can be disposed between the electrode body and the outer packaging body. Alternatively, the battery casing can be formed by a laminated film. The laminated film, for example, has a laminated structure having metal layers and resin layers stacked on top of each other. By overlapping and fusing the edges of the laminated film, a pouch-shaped battery casing can be formed.

[0060] In addition to the positive electrode plate, the electrode body may include a negative electrode plate and a separator. In the electrode body, the positive active material layer of the positive electrode plate and the negative active material layer of the negative electrode plate are separated by the separator. The electrode body can be a stacked type consisting of a positive electrode plate, a negative electrode plate, and a separator, or a wound type consisting of a long strip of stacked positive electrode plates, a negative electrode plate, and a separator wound together. The wound type electrode body may have a flat shape formed by pressing the long strip of stacked material after winding.

[0061] The negative electrode plate typically has a negative electrode current collector foil and a negative electrode active material layer. The negative electrode plate may have a negative electrode active material layer on one or both sides of the negative electrode current collector foil. The negative electrode current collector foil is, for example, a metal foil made of copper materials such as copper and copper alloys. The negative electrode active material layer contains a negative electrode active material, and further contains at least one of a conductive additive and a binder material, preferably both a conductive additive and a binder material.

[0062] The negative electrode active material includes at least one of carbon-based active materials and metal-based active materials, and may include both. As a carbon-based active material, examples include one or more carbon materials selected from graphite (such as natural graphite and artificial graphite), hard carbon, soft carbon, and amorphous coated graphite. As a metal-based active material, examples include elemental metals or metal oxides containing elements selected from silicon (Si), tin (Sn), antimony (Sb), bismuth (Bi), titanium (Ti), and germanium (Ge). The metal-based active material is preferably a Si-containing active material containing silicon (Si). The Si-containing active material preferably contains one or more of Si, SiOx (x = 0.5 to 1.5), and SiC, more preferably containing SiC, or is SiC. SiOx is preferably SiO.

[0063] The negative electrode active material preferably comprises carbon-based active material and Si-containing active material. This improves the volumetric energy density of the battery. The content of Si-containing active material in the negative electrode active material is preferably 3-15% by mass relative to the total amount of negative electrode active material, more preferably 5-15% by mass, and can be 5-10% by mass.

[0064] As conductive additives that may be included in the negative electrode active material layer, examples of conductive additives described herein that may be included in the positive electrode active material layer can be listed. As binders that may be included in the negative electrode active material layer, examples include cellulose-based resins such as carboxymethyl cellulose (CMC), methyl cellulose (MC), and hydroxypropyl cellulose; polyacrylic acid; and styrene-butadiene rubber (SBR). The binder may include one or more of these. As conductive additives, examples of the above-mentioned conductive additives can be listed, and the material may include one or more of the above-mentioned conductive additives.

[0065] A negative electrode plate can be obtained, for example, by forming a layer of negative electrode active material on a negative electrode current collector foil. For instance, a negative electrode plate is obtained by coating a negative electrode slurry containing a negative electrode active material onto a negative electrode current collector foil, drying and compressing it to form a layer of negative electrode active material. In addition to the negative electrode active material, the negative electrode slurry can contain conductive additives, binders, and solvents such as water.

[0066] The diaphragm (separator) has a substrate, and may have a functional layer on at least one side of the substrate. The substrate can be a membrane made of polyolefins such as polyethylene and polypropylene, resins such as polyester, cellulose, and polyamide, or a porous sheet such as nonwoven fabric. The substrate can be a single-layer structure or a multi-layer structure. Examples of functional layers include an adhesive layer and a heat-resistant layer, and one or both can be present. The adhesive layer can be formed using, for example, an adhesive. The heat-resistant layer can contain, for example, fillers and adhesives.

[0067] The non-aqueous electrolyte preferably contains an electrolyte in a non-aqueous solvent such as an organic solvent. Examples of electrolytes include LiPF6, LiBF4, LiClO4, LiFSO3, and LiBOB (lithium bis(oxalate)borate). The non-aqueous electrolyte may contain one or more of these electrolytes. Examples of non-aqueous solvents include ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), propylene carbonate (PC), butyl carbonate (BC), and diethyl carbonate (DEC). The non-aqueous electrolyte can contain one or more of these non-aqueous solvents. The non-aqueous electrolyte may further contain additives such as vinylene carbonate (VC), vinyl ethylene carbonate (VEC), and fluoroethylene carbonate.

[0068] Example

[0069] The following examples and comparative examples illustrate this disclosure in more detail.

[0070] [Preparation of lithium-excess active material (1)]

[0071] Active substance (1X):

[0072] [Composition] Li 1.17 Ni0.13 Co 0.13 Mn 0.57 O2

[0073] [Particle Morphology] Secondary particles formed by the aggregation of more than 50 primary particles (average particle size: small).

[0074] Active substance (1Y):

[0075] [Composition] Li 1.17 Ni 0.13 Co 0.13 Mn 0.57 O2

[0076] [Particle Morphology] Secondary particles formed by the aggregation of more than 50 primary particles (average particle size: large).

[0077] [Preparation of active material (2) with high nickel content]

[0078] Active substance (2X):

[0079] [Composition] LiNi 0.8 Co 0.1 Mn 0.1 O2

[0080] [Particle Morphology] Secondary particles formed by the aggregation of more than 50 primary particles (average particle size: large).

[0081] Active substance (2Y):

[0082] [Composition] LiNi 0.8 Co 0.1 Mn 0.1 O2

[0083] [Particle Morphology] Secondary particles formed by the aggregation of more than 50 primary particles (average particle size: small).

[0084] Active substance (2Z):

[0085] [Composition] LiNi 0.8 Co 0.1 Mn 0.1 O2

[0086] [Particle morphology] At least one of a single particle and a secondary particle formed by the condensation of 2 to 10 primary particles.

[0087] [Experimental Examples 1-13]

[0088] (Preparation of positive electrode active material)

[0089] A positive electrode active material was prepared using active material (1) and active material (2) as shown in Table 1. Active material (1) and active material (2) were mixed in such a way that the content of active material (1) in the positive electrode active material was as shown in Table 1.

[0090] (Making the positive electrode plate)

[0091] The prepared positive electrode active material, carbon nanotubes (CNTs) as conductive additives, polyvinylidene fluoride (PVdF) and N-methyl-2-pyrrolidone (NMP) as binders were mixed to obtain a positive electrode slurry. CNTs were prepared in proportions relative to the active material (1) as shown in Table 1, and PVdF was prepared in proportions of 1 part by mass relative to 100 parts by mass of the positive electrode active material. The positive electrode slurry was coated onto an aluminum foil used as the positive electrode current collector, dried, compressed to a specified thickness to form a positive electrode active material layer, and then cut to a specified size to obtain a positive electrode plate.

[0092] (Making the negative electrode plate)

[0093] As the negative electrode active material, a product was prepared by mixing graphite (a carbon-based active material) and SiC (a Si-containing active material) at a mass ratio of graphite:SiC = 95:5. This negative electrode active material, along with styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) as binders, was prepared at a mass ratio of negative electrode active material:SBR:CMC = 100:1:1. Water was then added to obtain a negative electrode slurry. The negative electrode slurry was coated onto a copper foil (used as the negative electrode current collector) and dried. After being compressed to a specified thickness to form a negative electrode active material layer, it was cut to a specified size to obtain a negative electrode plate.

[0094] (Battery cell fabrication)

[0095] For a polyethylene substrate, a two-layer separator with a heat-resistant layer including filler and adhesive was prepared. A positive electrode plate, a negative electrode plate, and a separator were stacked such that the positive active material layer of the positive electrode plate and the negative active material layer of the negative electrode plate were positioned opposite each other through the separator, with the positive active material layer in contact with the heat-resistant layer of the separator. The aluminum foil of the positive electrode plate and the copper foil of the negative electrode plate were exposed at both ends, thus obtaining an electrode body. The aluminum foil of the positive electrode plate of the electrode body was welded to an external aluminum current collector, and the copper foil of the negative electrode plate of the electrode body was welded to an external copper current collector. The electrode body was then inserted into the outer packaging of an aluminum laminate film, and the film was fused to form an injection port. A non-aqueous electrolyte was injected into the injection port, and after sealing the injection port, it was allowed to stand for 12 hours to obtain a battery cell.

[0096] The non-aqueous electrolyte is prepared as follows: Lithium hexafluorophosphate (LiPF6) is dissolved as the electrolyte in a mixed solvent in which ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) are mixed in a volume ratio of EC:EMC:DMC = 3:3:4.

[0097] [Determination of average particle size (D50)]

[0098] For active substances (1X), (1Y), (2X), (2Y), and (2Z), the average particle size (D50) was measured using a laser diffraction particle size distribution measuring device, and the ratio of the average particle size of active substance (2) to that of active substance (1) was calculated (average particle size (D50) of active substance (2) / average particle size (D50) of active substance (1)). The results are shown in Table 1. It should be noted that the average particle size (D50) of active substance (1X) is in the range of 1 to 4 μm, and the average particle size (D50) of active substance (2X) is in the range of 2 to 15 μm.

[0099] [Determination of volumetric energy density]

[0100] The discharge capacity of the battery cell was measured. Based on the discharge capacity, nominal voltage, and volume of the battery cell, the volumetric energy density [Wh / L] of the battery cell was calculated according to the following formula. The results are shown in Table 1.

[0101] Volumetric energy density [Wh / L] = Energy capacity [Wh] / Battery cell volume [L]

[0102] [In the formula, energy capacity [Wh] = discharge capacity of the battery cell [Ah] × nominal voltage [V].]

[0103] [Evaluation of Input / Output Characteristics]

[0104] Under conditions of 25℃, with a voltage range of 4.6–2.5V, charge and discharge were performed at 0.1C, and the voltage at 50% state of charge (SOC) was measured. At 50% SOC, charge and discharge were performed for 10 seconds each at rates of 0.33C, 0.5C, 1C, and 1.5C. The resistance value was calculated from the voltage change from 0 to 10 seconds at each rate. The results are shown in Table 1.

[0105] [Evaluation of Cyclic Characteristics]

[0106] Under conditions of 25°C, a voltage range of 4.6–2.5V was maintained, and charge-discharge treatment was performed at 0.1C. The discharge capacity was measured as the initial discharge capacity. Next, under conditions of 25°C, a voltage range of 4.6–2.5V was maintained, and charge-discharge treatment at 0.5C was repeated 100 times. Then, under conditions of 25°C, a voltage range of 4.6–2.5V was maintained, and charge-discharge treatment was performed at 0.1C. The discharge capacity was measured as the discharge capacity after cycle treatment. The capacity retention rate [%) was calculated based on the following formula. The results are shown in Table 1.

[0107] Capacity retention rate [%] = (Discharge capacity after cycle treatment / Initial discharge capacity) × 100

[0108] Table 1

[0109]

[0110] *1: Content of active material (1) when the positive electrode active material is set to 100% by mass

[0111] *2: Average particle size (D50) of active substance (2) / Average particle size (D50) of active substance (1)

[0112] *3: (CNT content in the positive electrode active material layer [parts by mass] / Content of active material (1) in the positive electrode active material layer [parts by mass]) × 100

[0113] The embodiments of the present invention have been described above. It should be considered that the embodiments disclosed herein are illustrative in all respects and are not restrictive. The scope of the present invention is defined by the claims and is intended to include all modifications within the meaning and scope equivalent to the claims.

Claims

1. A positive electrode active material comprising a first active material represented by formula (I) below and a second active material represented by formula (II) below, wherein both the first active material and the second active material are secondary particles formed by the aggregation of 50 or more primary particles, and the average particle size D150 of the first active material is smaller than the average particle size D250 of the second active material. Li 1+a1 Ni x1 Mr y1 M1 z1 O2(I) The 1+a2 Nor x2 Mn y2 M2 z2 O2(II) In equations (I) and (II), M1 and M2 are each independently one or more metallic elements selected from Co, Al, Mg, Ca, Ti, V, Cr, Fe, Cu, Zn, Zr, Nb, Mo, Ta, and W. Given the conditions 0.13≤a1≤0.33, 0≤x1≤0.3, 0.47≤y1≤0.67, and 0≤z1≤0.3, the expression a1+x1+y1+z1=1 is satisfied. -0.1≤a²≤0.1、0.6≤x²≤1、0≤y²≤0.3、0≤z²≤0.3, satisfying a²+x²+y²+z²=1.

2. The positive electrode active material according to claim 1, wherein, The average particle size D150 of the first active substance is 1–4 μm.

3. The positive electrode active material according to claim 1 or 2, wherein, The average particle size D250 of the second active substance is 2–15 μm.

4. The positive electrode active material according to claim 1 or 2, wherein, The ratio of the average particle size D250 of the second active substance to the average particle size D150 of the first active substance, D250 / D150, is greater than 2.

5. The positive electrode active material according to claim 1 or 2, wherein, The content of the first active substance is 60-95% by mass.

6. A positive electrode plate having a positive electrode active material layer comprising the positive electrode active material according to any one of claims 1 to 5.

7. The positive electrode plate according to claim 6, wherein, The positive electrode active material layer further comprises carbon nanotubes, and the content of the carbon nanotubes is 2 to 6% by mass relative to the total amount of the first active material in the positive electrode active material layer.

8. A non-aqueous electrolyte secondary battery comprising an electrode body having a positive electrode plate as described in claim 6 or 7.

9. The non-aqueous electrolyte secondary battery according to claim 8, wherein, The electrode body also includes a negative electrode plate with a negative electrode active material layer, the negative electrode active material layer containing a negative electrode active material, the negative electrode active material containing a carbon-based active material and an active material containing Si.

10. The non-aqueous electrolyte secondary battery according to claim 9, wherein, The content of the Si-containing active material in the negative electrode active material is 3 to 15% by mass relative to the total amount of the negative electrode active material.

11. The non-aqueous electrolyte secondary battery according to claim 9 or 10, wherein, The active substance containing Si is selected from one or more of Si, SiOx and SiC, wherein x = 0.5 to 1.5.

Citation Information

Patent Citations

  • Positive electrode for lithium ion battery and lithium ion battery using the same

    JP2012059527A